Ada Twist and the perilous pants - Beaty, Andrea (Beaty, Andrea. Questioneers, 2019)
"When Rosie Revere's Uncle Ned gets a little carried away wearing his famous helium pants, it's up to Ada and friends to chase him down. As Uncle Ned floats farther and farther away, Ada starts asking lots of questions: How high can a balloon float? Is it possible for Uncle Ned to float into outer space? And what's the best plan for getting him down?"--